Ionic Self‐Assembled Platform of Perylenediimide–Sodium Dodecylsulfate for Detection of Spermine in Clinical Samples. Issue 8 (29th March 2017) - Singh, Prabhpreet; Mittal, Lalit Singh; Bhargava, Gaurav; Kumar, Subodh
Abstract: The detection and quantification of spermine in clinical practice is important for early diagnosis of many diseases. Chromatographic and immunoassay‐based methods are commonly used. However, a fluorescence‐based assay could provide real‐time detection. Herein, the synthesis and aggregation properties of a dicationic perylene probe ( N 1 ‐dodecyl‐ N 3 ‐(4‐phenyl)benzimidazolium‐functionalized perylenediimide (DAB‐PDI )) used to develop a fluorescent "turn‐on" ensemble for the detection of spermine are discussed. The fluorescence ofDAB‐PDI (10 μm, Φ =0.55) is efficiently quenched by negatively charged sodium dodecylsulfate (SDS) through the formation of ionic self‐assembled aggregates (charge ratio of negative (N) in SDS to positive (P) inDAB‐PDI (N/P)=9). This negatively charged ionic self‐assembly betweenDAB‐PDI and SDS has been characterized by using photophysical, microscopic, dynamic light scattering, isothermal titration calorimetry, and HRMS techniques. The addition of spermine to this ensemble solution results in the breakdown of theDAB‐PDI –SDS ensemble owing to strong binding of spermine with SDS and, as a result, the fluorescence ofDAB‐PDI is recovered. This ensemble exhibits high sensitivity and selectivity for spermine detection in water, urine, and blood serum. The lowest limit of detection is 27.5 nm, which is at least about 36 times lower than that required for early diagnosis of cancer (1 to 10 μm for urinary spermine). Abstract : Sight for sore eyes ! The ionic self‐assembly of amphiphilic N 1 ‐dodecyl‐ N 3 ‐(4‐phenyl)benzimidazolium‐functionalized perylenediimide (DAB‐PDI ) with sodium dodecyl sulfate (SDS) exhibits selectivity for the detection of spermine (limit of detection=27.5 nm ) in urine and blood serum (see figure).